The situation of the third sector in Ecuador: Survival of NGOs in an adverse environment - Gortaire-Morejón, Bernardo (2022)
Of the 4,939 non-governmental organizations (NGOs) registered in 2020 in Ecuador, less than one third known to be in operation, one third have ceased to operate and the other third provide no information about their functioning. These figures reflect the dire reality of the third sector in Ecuador, which is the subject of analysis in this article. On the one hand, the situation highlights the shortcomings of the state in responding to the needs of its population; on the other hand, it reveals so-called "NGOism", a situation in which the role of NGOs has become overextended. Through the description and analysis of data, this text addresses the crisis in this sphere of citizen participation, which is limited to a few professionalized actors in permanent competition with dozens of local organizations. It describes a scenario of scarce opportunities to obtain funding, as well as the presence of NGOs in digital media, which engenders the dissemination of their work and their legitimization. It is concluded that these figures reflect the need to implement strategies to strengthen the dynamics of the third sector, so that the state, the private sector and the agents that constitute the world of foundations and NGOs offer a genuine response to social problems.